Influence of ICTs use on livelihood resilience mediated by flood risk perception among fishermen in the east coast of Malaysia - Garba, Bashir Muktar (2018)
Small-scale fisheries are important socio-ecological systems contributing towards the attainment of food security, economic wealth and social well-being in Malaysia. They provide about 65% protein requirements of the population while extending a lot of employments opportunities across the fish value chain. However, climate change and extreme events are threatening the sustainability of fishing activities. Climate extreme events like flood disrupts and destroys assets thereby undermining fishing community’s developmental gains and livelihoods. Malaysian governments’ effort to reduce fishermen’s vulnerability towards sustainable productivity, has promoted the use of Information Communication Technologies (ICTs) in the fishing sector. Hence, ICTs are utilized in all stages of fish value chain, from sourcing climate information, advisory services, navigation, down to e-declaration of catches and linkages to markets. Such information as key input to adaptation for Livelihood Resilience (LR) are disseminated through various ICTs. Yet, an unresponsiveness and unprepared attitude by fishermen towards flood risks communication is reported. Generally, the reactive rather than proactive flood management in the country suggests an unsustainable top-down approach. Furthermore, a paucity of empirical evidences on influences of use of ICTs on LR limits informed planning by authorities. This research, utilized Sustainable Livelihood Framework and Protective Motivation Theory to contribute to literature. It highlights access, utilization of ICTs and preferences (bottom-up input) for flood risks communication. It identified underlying structures for measuring LR and how flood risk perception mediates the relationship between use of ICTs and LR. Through a stratified random sampling and proportionate distribution in three states of east-coast Malaysia (Terengganu, Pahang and Kelantan states), data were collected using self-administered questionnaire to a randomly drawn sample size of 380 fishermen. Descriptive statistics facilitates the categorization of socio-economics characteristics, levels of LR and perceived importance-performance of risks communications. Results reveals 52.2 % fishermen have low and another 40.9% have moderate LR. 65.5% perceived flood risk communication is important and 64.4% rated the flood risk communication as satisfactorily. Factor analysis reveals five factors with total explained variance of 72.893%, KMO of .878 indicating sufficient inter-correlations and adequacy of sample studied while the Bartlett’s test of sphericity was significant (Chi square= 4836.384, P<0.00). The Structural Equation Modelling analysis reveals insignificant relationship between use of ICTs and LR, indicative of full mediation of flood risk perception. The results suggest that fishermen’s specific need of information should be provided through the discovered preferred ICTs. The interaction among variables and the identified influence of the mediator extends an insight into the influence of ‘cognitive processes’ towards flood preparedness action for LR enhancement. This is a valuable input in flood risk management and other policy formulation on communication for behavioural change in agricultural communities. Detailed assessments within this research provide valuable input in all the five steps of developing National Adaptation Communication Strategy as recommended by United Nations. The integrated model has also presented a framework for understanding influences of ICTs mediated communication on cognitive appraisal of ‘risk perception’ towards sustainable behaviour change. The academics and practitioners can use this findings and frameworks for further research and also as a baseline for a longitudinal form of studies.